Manajemen strategi dalam menghadapi pesaing bisnis melalui analisis SWOT - Alisa, Siti Nur (Maliki Interdisciplinary Journal, 2025)
Strategic management is a plan developed by a company to optimize its operations. With an effective strategy, the company can face fierce global competition. Competitors pose a threat to the company, and how the company can maintain quality and optimize its performance to remain productive in the global market. Corporate strategic management uses SWOT analysis (Strength, Weakness, Opportunity, Threat). SWOT analysis helps companies develop appropriate strategies to achieve their long-term and short-term goals. With this analysis theory, companies can analyze problems in the global market. With this analytical theory, companies can analyze problems in the global market. Based on this analysis, companies can then formulate offensive strategies (capitalizing on strengths and opportunities) and defensive strategies (overcoming weaknesses and threats). Measurable strategy implementation and ongoing evaluation are key to ensuring that companies can not only survive but also excel and grow sustainably in dynamic global competition.